L’arte dell’inganno: Machiavelli and the Execution of the Florentine Captain-General Paolo Vitelli - Mitrovic, Milos (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
This article addresses Niccolò Machiavelli’s role in a five-century-long controversy surrounding the execution of the Florentine captain-general Paolo Vitelli in October 1499. The official letters and dispatches Machiavelli wrote shortly before and after the event portrayed Vitelli as a traitor, thus defending the Signoria’s decision to execute the captain. In chapter 12 of The Prince, however, Machiavelli changes his tone, implying that it was not the alleged treason but the captain’s fame and Florentine insecurity that lead to his death. Given that many contemporaries praised Vitelli and seriously doubted his guilt, Machiavelli’s ambivalent positioning requires explanation. By way of the first sustained analysis of the Vitelli affair, this article will shed new light on Machiavelli’s early involvement in Florence’s political machinations. It will show how Machiavelli, as a loyal servant to his beloved Republic, coordinated, defended, and justified in his writings the course of action against Vitelli.